LAW, RELIGION, AND FREEDOM (ABINGDON)
1 online resource
Keywords: This book examines major conceptual challenges confronting freedom of religion or belief in contemporary settings. The volume brings together chapters by leading experts from law, religious studies, and international relations, who provide perspectives from both sides of the Atlantic. At a time when the polarization of culture wars' is aggravating tensions between secular and religious views about accommodating the conscientious claims of individuals and groups, and when the right to freedom of religion itself is facing misunderstanding and erosion, the work provides welcome clarity and depth. Some chapters adopt a primarily conceptual and historical approach; others analyze particular difficulties or conflicts that have emerged in European and American jurisdictions, along with concrete applications and recommendations for the future. The book will be a valuable resource for students, academics, and policy-makers with an interest in law, religion, and human rights.